IMPLEMENTASI KECERDASAN EMOSIONAL DALAM KEPEMIMPINAN PENDIDIKAN - Malik, Amarullah (Manajerial | Journal Manajemen pendidikan islam, 2025)
Educational leadership that has the criterion of emotional quotient is the leader with the ability to influence the educational community through self-awareness and self-management. This ability helps school leaders to understand the society. In other words, the leader has the social awareness and skill management. It is the skill to interact with the shcool community their wants. In addition, the school leaders are required to be honest to their selves and the whole educational community for their building of self strength, self-conscience, honor, and responsibility to the whole school community. To conclude that the cooperation between leaders and society (social community) the goal of the education will be achieved.